Alternatives To Infrastructure Privatization Revisited : Public Enterprise Reform From The 1960s To The 1980s - A. Gomez-Ibanez, Jose (The World Bank, 2007)
Frustration with the performance of State-owned enterprises (SOEs) has led to two rounds of reform: the first round, from the 1960s through the 1980s, attempted to improve SOE performance while maintaining public ownership while the second, beginning in the late 1980s, viewed privatization as the answer. Interest in the earlier round of reform has increased recently as controversy has slowed or halted privatization in many countries, especially for SOEs providing infrastructure services that are basic to everyday life and are thought to have elements of monopoly. This paper reexamines the earlier round of reforms, focusing particularly on efforts to increase the firms' capacity with infusions of human and physical capital, to strengthen managerial incentives through performance contracts and corporatization and to alter the mix of political and economic forces that impinge on the firm by strengthening the involvement of taxpayers, customers or private investors. The review suggests that these earlier approaches generated only modest success but that some of them, selectively applied, may be helpful in improving the performance of infrastructure firms that remain in public hands